1991
DOI: 10.1093/jac/27.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of amoxycillin/clavulanic acid in experimental Staphylococcus aureusendocarditis in the rat

Abstract: The efficacy of amoxycillin/clavulanic acid was compared with that of flucloxacillin, vancomycin and amoxycillin in an experimental model of Staphylococcus aureus endocarditis. Doses of the antibiotics were selected to produce peak concentrations in rat serum similar to those achievable in man after administration of parenteral therapeutic doses. Amoxycillin clavulanic acid was more effective than amoxycillin alone against endocarditis caused by beta-lactamase producing strains of Staph. aureus, illustrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This relatively poor activity of vancomycin has been demonstrated in other S. aureus endocarditis studies, both in rats (3)(4)(5) and in rabbits (6,8). It has also been reported that in vitro vancomycin may kill S.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This relatively poor activity of vancomycin has been demonstrated in other S. aureus endocarditis studies, both in rats (3)(4)(5) and in rabbits (6,8). It has also been reported that in vitro vancomycin may kill S.…”
Section: Discussionmentioning
confidence: 63%
“…The combination of clavulanic acid with amoxicillin has been shown to be effective in rats against early endocarditis in which the vegetations contained approximately 6 to 8 log1o CFU of S. aureus per g (3,5) and against late S. aureus endocarditis in which bacterial counts were 9 to 10 log1o CFU/g (5). The activity of a combination of clavulanic acid with ticarcillin against S. aureus endocarditis in rabbits has been reported elsewhere (7,24).…”
mentioning
confidence: 95%
“…Only a few clinical and in vitro studies have, however, tried to assess the potential of amoxycillin clavulanic acid in severe staphylococcal infections as compared to other antistaphylococcal drugs. In experimental animal models, amoxycillin-clavulanic acid has been found just as effective as cloxacillinlflucloxacillin for staphylococcal endocarditis (13,14) and at least as effective in osteomyelitis (1 5). Moreillon has in a clinical study of patients with endocarditis found evidence that amoxycillin-clavulanic acid is effective in such infections (16).…”
Section: Discussionmentioning
confidence: 99%